2015
DOI: 10.1016/j.niox.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute dietary nitrate supplementation improves arterial endothelial function at high altitude: A double-blinded randomized controlled cross over study

Abstract: Acute dietary NOsupplementation may abolish altitude-induced reduction in endothelial function, and can serve as a dietary strategy to ensure peripheral vascular function in lowland subjects entering high altitude environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 46 publications
6
53
1
2
Order By: Relevance
“…Conversely, from 3 to 15 days of progressive hypobaric hypoxic exposure (the time frame of our study), NO bioavailability is in fact elevated compared to the normoxic situation (4; 24) , likely due to an upregulation of the NOS-NO system, which may cause any additional NO production via alternative pathways to be less potent, potentially explaining why beetroot supplementation failed to alter the outcomes in the current study. This explanation is not supported by results that found beetroot juice supplementation to improve endothelial function at 3700 meters after 3 days of trekking from lower altitude (15) . An alternative explanation is that dietary nitrate supplementation does not alter any of the specific variables we measured involved with hypoxic acclimatisation; heart rate, blood pressure, SpO 2 , and ventilation rate.…”
Section: Accepted Manuscriptmentioning
confidence: 76%
See 1 more Smart Citation
“…Conversely, from 3 to 15 days of progressive hypobaric hypoxic exposure (the time frame of our study), NO bioavailability is in fact elevated compared to the normoxic situation (4; 24) , likely due to an upregulation of the NOS-NO system, which may cause any additional NO production via alternative pathways to be less potent, potentially explaining why beetroot supplementation failed to alter the outcomes in the current study. This explanation is not supported by results that found beetroot juice supplementation to improve endothelial function at 3700 meters after 3 days of trekking from lower altitude (15) . An alternative explanation is that dietary nitrate supplementation does not alter any of the specific variables we measured involved with hypoxic acclimatisation; heart rate, blood pressure, SpO 2 , and ventilation rate.…”
Section: Accepted Manuscriptmentioning
confidence: 76%
“…Conversely, during more sustained hypoxic exposure (a six week normobaric hypoxic training regime), exercise performance was not altered by nitrate supplementation (14) . The only study describing the effects of oral nitrate supplementation on physiological responses to high altitude exposure found a single beetroot juice drink (5 mmoles) restored endothelial function to pre-trek levels following 3 days of trekking from 1523 to 3700 meters (15) . These studies demonstrate that nitrate supplementation can effectively alter physiological responses to acute normobaric and hypobaric hypoxia.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Nevertheless, further research is warranted to confirm whether the beneficial effects of NO3 supplementation observed in the present investigation also manifest at terrestrial altitude. It is noteworthy that one recent study reported improvements in flow mediated dilation (FMD) following NO3 ingestion during a trek to 3,700 m terrestrial altitude (Bakker et al, 2015), suggesting the potential capacity to alter some physiological parameters at genuine high altitude with this supplement. The relatively modest sample size of the present study may also be regarded as a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Elevating NO bioavailability via NO3 supplementation has been reported to restore muscle metabolic function and leg-extension TTE to normoxic levels during exposure to moderate simulated altitude (i.e., normobaric hypoxia; fraction of inspired oxygen (F I O 2 ): 14.5%; ~2,800 m) (Vanhatalo et al, 2011). Others have also observed increased peripheral oxygen saturation (SpO 2 ) (Masschelein et al, 2012; Muggeridge et al, 2014; Bourdillon et al, 2015; Shannon et al, 2016), elevated muscle oxygenation (Masschelein et al, 2012), improved endothelial function (Bakker et al, 2015), and enhancements in high-intensity TTE (Vanhatalo et al, 2011; Masschelein et al, 2012; Kelly et al, 2014) and TT performance (Muggeridge et al, 2014; Shannon et al, 2016) across a range of altitudes/ simulated altitudes (F I O 2 : 11–15%; 2,500–5,000 m) consequent to NO3 supplementation. Interestingly, one study reported that NO3 supplementation was more effective in normobaric hypoxia (F I O 2 13.1%; ~3,700 m) compared with normoxia (Kelly et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nitric oxide (NO) is a pleiotropic signaling molecule and a regulator of multiple physiological processes, many of which are altered by hypoxia, including mitochondrial function [13, 14], cerebral and muscle tissue blood flow [1517], muscle metabolism [10, 11], and endothelial function [18, 19]. NO plays a fundamental role in the response to hypoxia and has been implicated in hypoxia-induced vasodilation, a mechanism designed to ensure appropriate matching between O 2 delivery and the metabolic demands of muscle and cerebral tissue when O 2 availability is low [15, 20].…”
Section: Introductionmentioning
confidence: 99%